Influence of norms of fertilizers and the mode of irrigation on the productivity of cotton plant - Сейидалиев, Н. Я. (Scientific Progress & Innovations, 2012)
The efficiency of using fertilization and irrigation regime on the abscission of plant organs and on the mass of one cotton box has been studied in bifactorial field experiment in Mil - Garabagh valley. It was determined that these two factors influenced economical and biological indices. The maximal increase due to effective norms of fertilizers application is observed.